(untitled) (Journal of actual problems of jurisprudence, 2018)
The article attempts to generate categorical and conceptual apparatus of migration crime, accompanying the migration process, the allocation of a certain set of attributes and an attempt to present a migration crime in the form of a definition. Migration crime acts as a specific subsystem of crime in general, are closely related. Vector directional migration of crime give migrants. Migration crime exists as a certain integrity, consisting of separate elements, allocated on the basis of a single criterion – the characteristics of the behavior of the subject of the crime of violation of immigration legislation or migration. Key words: migration crime, criminal migration, crime associated with migration, crime migrants, criminality of foreigners.